2004
DOI: 10.1242/dev.01200
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty proteins regulate ureteric branching by coordinating reciprocal epithelialWnt11, mesenchymalGdnfand stromalFgf7signalling during kidney development

Abstract: the early stages of organogenesis indicated a crucial role for sprouty function in coordination of epithelialmesenchymal and stromal signalling, the sites of expression of these genes. Moreover, Fgf7 induced Spry2 gene expression in vitro and led with Gdnf to a partial rescue of the SPRY2-mediated defect in ureteric branching. Remarkably, it also led to supernumerary epithelial bud formation from the Wolffian duct. Together, these data suggest that Spry genes contribute to reciprocal epithelialmesenchymal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 68 publications
4
84
0
Order By: Relevance
“…Another interesting study on FGF7 in the context of a negative factor was recently published. 28 In that study, overexpression of Spry in the WD resulted in defective branching morphogenesis of the UB. In the mutant kidney/WD culture, administration of FGF7 not only rescued branching of the UB (consistent with in vitro data 12 ) but also induced ectopic bud formation from the WD.…”
Section: Discussionmentioning
confidence: 84%
“…Another interesting study on FGF7 in the context of a negative factor was recently published. 28 In that study, overexpression of Spry in the WD resulted in defective branching morphogenesis of the UB. In the mutant kidney/WD culture, administration of FGF7 not only rescued branching of the UB (consistent with in vitro data 12 ) but also induced ectopic bud formation from the WD.…”
Section: Discussionmentioning
confidence: 84%
“…Loss of spry2 in mice resulted in enteric nerve hyperplasia due to excessive GDNF signaling. 34 In the chick embryo, Spry2 expression in the isthmus was shown to contribute to the regionalization of the presumptive mesencephalon and metencephalon, the latter giving rise to the future cerebellum. 35 The data obtained in this study suggest that Spry2 also participates to the control of neurite growth.…”
Section: Discussionmentioning
confidence: 99%
“…45 Recently, Maeshima et al showed that Fgf7, induced UB outgrowth in Ret null WDs when activin signaling was inhibited. 53 Conclusive evidence for participation of other RTKs in the network of Ret-Spry1 in the early events of WD growth to sculpt the metanephric kidney would require generation of multiple mutant alleles including Fgf pathway mutants, Spry1 and Ret signaling mutants.…”
Section: The Role Of Specific Ret-activated Pathways In Cakut Pathogementioning
confidence: 99%
“…52 Chi et al demonstrated interactions between Gdnf, Fgf7, Wnt11 and Spry signaling by showing that renal include activating factors upstream, either in the MM or in mesonephric mesoderm influencing Ret activity through Gdnf or in the UB, and downstream of Ret such as Wnt11 (forms a positive feedback loop), and repressors such as Spry in the WD or metanephros. 45 I will briefly review examples where direct evidence of genetic interactions between Ret signaling complex and other genes has been observed in vivo. One of the first examples of this came from studies of Spry1 null and Gdnf heterozygous animals.…”
Section: Genetics Of Cakutmentioning
confidence: 99%
See 1 more Smart Citation